Protection effect of overwintering water bird habitat and defining the conservation priority area in Poyang Lake wetland, China - Chuanzhun Sun; Hannes J König; Sandra Uthes; Cheng Chen; Peng Li; Karoline Hemminger (Environmental Research Letters, 2020)
Biodiversity conservation is one of the most important objectives of protected areas. Most biodiversity assessment-related studies use the change in species abundance data to measure the level of biodiversity conservation. Yet for many areas, long-term species data are not available and thus it is necessary to use biodiversity indices to monitor the effect of land use (LU) changes or the impact of protected area establishment. Poyang Lake wetland is one of the most important wintering sites for migratory water birds on the East Asian–Australasian flyway. To protect this habitat, 14 nature reserves were created in the region between 1997 and 2003. This paper aims to assess the effect of nature reserve creation on the status of habitat for overwintering water birds in Poyang Lake wetland by analysing LU and land cover data from 1995, 2005 and 2015. We developed a composite biodiversity index to search for current biodiversity hotspots (conservation priority) in the study area. An integrated approach consisting of the Integrated Valuation of Ecosystem Services and Trade-offs model, GIS, fragment analysis and hotspot analysis was used to realize our objective. Our results showed that the creation of the nature reserve had positive effects on overwintering water bird habitat. However, tremendous changes (such as change of habitat area, quality and fragmentation) within and outside the nature reserve showed that the role of protected area still needs to be further discussed. Moreover, regional synthesis LU management plans such as ecological restoration should be carried out. The results of the habitat assessment also indicate that a comprehensive biodiversity index framework based on net primary productivity, habitat connectivity and habitat quality could be more efficient in assessing biodiversity and defining a reasonable protected area, from data obtain in large scale perspective.